2016
DOI: 10.7307/ptt.v28i2.1811
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Decision-Making Algorithm for Automatic Lane Change Manoeuvre Considering Traffic Dynamics

Abstract: This paper proposes a novel algorithm for decision-making on autonomous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…The gap acceptance criterion for the on-ramp CAV is that its current and predicted inter-vehicle time gaps to its future direct predecessor and follower in the whole prediction horizon T p are larger than a certain time gap, depending on the on-ramp vehicle's location on the acceleration lane. When the on-ramp CAV's lane-changing initiation time is given, its lateral motion is modeled with a lateral trajectory equation [28], which is elaborated in Appendix A. The operational layer controller updates its commands with a fixed frequency 1/t.…”
Section: Cooperative Merging Control Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The gap acceptance criterion for the on-ramp CAV is that its current and predicted inter-vehicle time gaps to its future direct predecessor and follower in the whole prediction horizon T p are larger than a certain time gap, depending on the on-ramp vehicle's location on the acceleration lane. When the on-ramp CAV's lane-changing initiation time is given, its lateral motion is modeled with a lateral trajectory equation [28], which is elaborated in Appendix A. The operational layer controller updates its commands with a fixed frequency 1/t.…”
Section: Cooperative Merging Control Architecturementioning
confidence: 99%
“…When the on-ramp vehicle starts to change lane, i.e. ξ r (t) = 1, its lateral path during the lane changing process is designed to follow a polynomial equation [28], as shown in (21) and (22) in Appendix A.…”
Section: B Operational Layer Controller Regulating Vehicular Trajectmentioning
confidence: 99%
“…The implemented lane change behavior in Vissim is based on the lane change algorithm described in [39] and [40]. Based on this research, the trajectory equation for the lane change can be derived in the displacement of the vehicle from the center of the lane in terms of time.…”
Section: F Lane Change Behaviormentioning
confidence: 99%
“…where (x s rr , y s rr ) and (x D lf , y D lf ) can be determined using equations (16) and (25), respectively.…”
Section: Trajectory Planningmentioning
confidence: 99%
“…This strategy provided safe lane change manoeuvre considering some safety constraints, which were based on kinematics and dynamics of the passenger car and environment conditions. 25 Then, Shojaei et al developed this methodology for a constant speed articulated vehicle for single and double-lane-change manoeuvre considering the constant speed surrounding vehicles in manoeuvre. The obtained results demonstrated that the method could be implemented as a safe and feasible manoeuvre for the constant speed articulated vehicle in real traffic conditions.…”
Section: Introductionmentioning
confidence: 99%